Contemporary Europolicy in the Context of the Green Deal - Karpuzova, Mina (Economy and Business Yearbook, 2022)
The energy crisis and the environmental problems facing the modern community require modernization of the legislative framework and the introduction of more effective, sustainable, and ecological measures to preserve the health of people and the planet. The paper examines the contemporary European policies in the context of the Green Deal, emphasizing their possible impacts on the Bulgarian economy. The Green Deal is one of the key European documents which combats climate change and aimed the decarbonization of Europe, by implementing sustainable development, circular business models, new technologies and innovations, and new legislative measures. Certainly, for every single transformation, in addition to positives, there are also possible negatives, therefore the transition to sustainable development and circular economy must be carried out at all economic and institutional levels, based on the analyzes and assessments made in advance.